Menilai Kemahiran Bahasa Inggris Pemandu Wisata di Penglipuran: Perspektif Kompetensi Komunikatif - Luh Sri Damayanti (ELTIN Journal, 2025)
English skill is an essential skill for those who work in tourism sector, as the tour guides in Penglipuran Village. This study investigated the English language proficiency of tour guides in Penglipuran Village, Bali, with a specific focus on communicative competence. The research was a quantitative study by employing Canale and Swain's model as a framework. The research assessed tour guides' grammatical, sociolinguistic, discourse, and strategic abilities. Data were collected through questionnaires. The questionnaires were distributed to five tour guides. Findings indicate that while the tour guides exhibited a generally good command of English grammar and vocabulary, challenges emerged in areas such as complex sentence construction, idiomatic expressions, and handling unexpected tourist inquiries. Although the tour guides demonstrated a strong ability to adapt to different communication situations, there is room for improvement in terms of expanding vocabulary and enhancing cultural awareness to provide a more enriching tourist experience. The study underscores the importance of ongoing language training programs tailored to the specific needs of tourism professionals.